Targeted gold nanoparticles enable molecular CT imaging of head and neck cancer: An in vivo study. (September 2019) - Khademi, Sara; Sarkar, Saeed; Shakeri-Zadeh, Ali; Attaran, Neda; Kharrazi, Sharmin; Ay, Mohammad Reza; Azimian, Hosein; Ghadiri, Hossein
Graphical abstract: Highlights: FA-Cys-AuNPs can be employed as a promising contrast agent in CT scan imaging. CT values of targeted cells are 2-times higher than that of non-targeted nasopharyngeal cancer cells in nude mice. FA-Cys-AuNP reveals good blood compatible property. Abstract: The development of various cost-effective multifunctional contrast agent for specific targeting molecular imaging of tumors presents a great challenge. We report here the in vivo targeting imaging of folic acid (FA) gold nanoparticles (AuNPs) through cysteamine (Cys) linking for targeted of human nasopharyngeal head and neck cancer by computed tomography (CT). The toxicity of nanoparticles in kidney, heart, spleen, brain and liver was evaluated by H&E (hematoxylin and eosin) assay. We showed that the formed FA-Cys-AuNPs with an Au core size of ˜13 nm are non-cytotoxic in the particle concentration of 3 × 10 3 μg/ ml. The nude mice were scanned using a 64-slice CT scan with parameters (80 kVp, slice thickness: 0.625 mm, mAs: 200, pitch: 1). CT scan was performed before and after (Three and six hours) I.V (Intra Venous) injection of AuNPs and FA-Cys-AuNPs. The distribution of nanoparticles in the nude mice was evaluated by imaging and coupled plasma optical emission spectrometry (ICP-OES) analysis. The findings clearly illustrated that a small tumor, which is undetectable via computed tomography, is enhanced by X-ray attenuation and becomes visible (4.30-times) by the molecularly targeted AuNPs. It was further demonstrated that active tumor cells targeting (FA-Cys-AuNPs) is more specific and efficient (2.03-times) than passive targeting AuNPs. According to the results, FA-Cys-AuNPs can be employed as a promising contrast agent in CT scan imaging and maybe in radiotherapy that require enhanced radiation dose.